The Thoughts of Yūsuf al-Qarḍāwī and Ahmad Hassan in a Comparative Study of Usury Hadiths - Mochamad Varendy (مجلة النور الدولية للقرآن والحديث, 2024)
Yūsuf al-Qarḍāwī and Ahmad Hassan are prominent scholars who have an essential role in the development of Islam. These two figures have extraordinary thoughts in the fields of hadith, tafsir, and fiqh. Yūsuf al-Qardhawi's thoughts on the issue of usury are different from Ahmad Hassan's thoughts. This research aims to determine the differences and similarities in the thoughts of the two figures. The research method used is library study; the data sources come from articles, books, and other readings. The analysis results in this study show that in their thinking, both figures agree that the law of usury is haram. However, according to Yūsuf al-Qardhawi, it can be considered usury if everything contains an additional amount that exceeds the original amount without exception. At the same time, Ahmad Hassan's usury only occurs in matters of borrowing and lending. Apart from that, something where there is an excess in an amount is not included in usury.